Bacterial oxidation in the hydrometallurgical process of copper extraction from copper-containing ore - Kenzhaliyev Bagdaulet Kenzhalievich; Koizhanova Aigul Kairgeldyevna; Bakrayeva Akbota Nurdildakyzy; Magomedov David Rasimovich; Yerdenova Mariya Beisenbekovna; Abdyldayev Nurgali Nurlanovich (Researcher and Lecturer Society, 2024)
Copper extraction technologies are constantly being improved including chemical oxidants. However, chemical oxidants slightly increase the extraction. Thus, this study aims to increase copper extraction using bacterial oxidation as oxidizing reagent. It also compares extraction results between standard leaching with sulfuric acid and Acidithiobacillus ferrooxidans with amino acids nutrient medium. Ore from Zhezkazgan deposit that contains chrysocolla, malachite and iron hydroxide was used as a sample. The ore was dug from a 6m depth. The initial sample was crushed, grinded, mixed, and reduced before preliminary biooxidation by bacterial culture of Acidithiobacillus ferrooxidans. A mineralogical study of ore was conducted to confirm the copper contains, other compounds and phase composition as well. Acidithiobacillus ferrooxidans were cultured within the nutrient medium of amino acid. This study chooses amino acid serine L, glycine, and asparagine to provide optimum bacterial cell of A. Ferrooxidants. Results showed that preliminary biooxidation by bacterial culture of A.Ferrooxidans increased copper extraction significantly. Further, Acidithiobacillus ferrooxidans that grow in the nutrient medium containing L-Serine have the highest effect on copper extraction.